Personal Construct Therapy vs Cognitive Behavioral Therapy in the Treatment of Depression in Women with Fibromyalgia: Study Protocol for a Multicenter Randomized Controlled Trial - Paz, Clara (Neuropsychiatr Dis Treat, 2020)
Background: Fibromyalgia (FM) is a debilitating syndrome, more prevalent in women, which is aggravated by the presence of depressive symptoms. In the last decade, cognitive behavioral therapy (CBT) has demonstrated to reduce such depressive symptoms and pain in these patients, but there are still a considerable number of them who do not respond to interventions. The complexity of the disorder requires the consideration of the unique psychological characteristics of each patient to attain good outcomes. One approach that could accomplish this goal might be personal construct therapy (PCT), an idiographic approach that considers identity features and interpersonal meanings as their main target of intervention. Then, the aim of the study is to test the efficacy of PCT as compared to a well-established treatment in the reduction of depressive symptoms in women with fibromyalgia. METHODS AND ANALYSIS: This is a multicenter randomized controlled trial. In each condition participants will attend up to eighteen 1-hr weekly therapy sessions and up to three 1-hr booster sessions during the following 3–5 months after the end of treatment. The depression subscale of the Hospital Anxiety and Depression Scale (HADS-D) will be the primary outcome measure and it will be assessed at baseline, at the end of therapy, and at 6-month follow-up. Other secondary measures will be applied following the same schedule. Participants will be 18- to 70-years-old women with a diagnosis of FM, presenting depressive symptoms evinced by scores above seven in depression items of the HADS-D. Intention-to-treat and complete case analyses will be performed for the main statistical tests. Linear mixed models will be used to analyze and to compare the treatment effects of both conditions. TRIAL REGISTRATION: ClinicalTrials.gov: NCT02711020.